Hypoxia-Induced ROS Contribute to Myoblast Pyroptosis during Obstructive Sleep Apnea via the NF-κB/HIF-1α Signaling Pathway. (11th December 2019) - Yu, Li-Ming; Zhang, Wei-Hua; Han, Xin-Xin; Li, Yuan-Yuan; Lu, Yun; Pan, Jie; Mao, Jia-Qi; Zhu, Lu-Ying; Deng, Jia-Jia; Huang, Wei; Liu, Yue-Hua
Abstract : Tissue hypoxia caused by upper airway collapse is a main cause of excessive oxidative stress and systemic inflammation in obstructive sleep apnea (OSA) patients. Increased reactive oxygen species (ROS) and inflammatory responses affect cell survival and ultimately contribute to tissue injury. In the present study, we proposed that the induction of ROS by hypoxia, as an intrinsic stress, activates myoblast pyroptosis in OSA. We found increased cell death and abnormal expression of pyroptosis markers in the skeletal muscle of OSA mice. In vitro studies showed hypoxia-induced pyroptotic death of C2C12 myoblasts, as evidenced by the activation of caspase-1 and gasdermin D (GSDMD). Hypoxia induced ROS overproduction and accumulation in myoblasts. More importantly, applying N-acetylcysteine (NAC), an ROS scavenger, rescued cell swelling, downregulated the inflammatory response, and prevented pyroptotic death in hypoxia-cultured myoblasts. Hypoxia stimulation promoted NF- κ B P65 phosphorylation and HIF-1 α nuclear translocation. Moreover, hypoxia increased the nuclear level of cleaved caspase-1 and GSDMD. NAC inhibited hypoxia-induced variations in the HIF-1 α and NF- κ B signaling pathway. Taken together, our results determined that hypoxia-induced ROS contribute to myoblast pyroptosis. Therefore, our findings suggest that ROS may be a potential therapeutic target for ameliorating hypoxia-induced cell death and tissue injury, especially in OSA and hypoxia-related diseases.